Fundamentos de las cuentas por finalidad del gasto público (2010)
This paper is a thematic revision of the main concepts concerning theoretical approaches and empirical evidences of public expenditures according to the fundamental aims from the public decision making processes. One of the foremost aspects here discussed is that the Colombian public accountability system does not have statistical data neither accounts in terms of effective cash operations, as indicators for national budget expenditures. Within the analysis of this study a methodological perspective aimed to be applied worldwide by the United Nations Organization is used. This methodology is also recommended by the International Monetary Fund to establish national accountability systems following Europeans achievements in this sphere. Many countries in the world have already adopted this sort of system. Affecting its implementation one can see factors such as the Colombian legal conditions, current conditions of public institutions, and the requirement of a normative framework for national accounts according to the availability of applicable data